2014
DOI: 10.1097/psy.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Telehealth Coping Skills Intervention on Outcomes in Chronic Obstructive Pulmonary Disease

Abstract: Objective Chronic obstructive pulmonary disease (COPD) is associated with increased morbidity and mortality and reduced quality of life. Novel interventions are needed to improve outcomes in COPD patients. The present study assessed the effects of a telephone-based coping skills intervention on psychological and somatic quality of life and on the combined medical endpoint of COPD-related hospitalizations and all-cause mortality. Methods We conducted a dual-site, randomized clinical trial with assessments at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 75 publications
0
64
0
1
Order By: Relevance
“…30,33,35,36,38,41,45,47,49,56,57 mHealth enables selfmonitoring, self-management, self-medication, overcomes issues of anxiety that can be experienced in crowded environments such as clinics, hospitals or even malls, and it enables patients to live alone and increase their health literacy. Themes of understanding and visibility were mentioned in 8/60 occurrences (13%).…”
Section: Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,33,35,36,38,41,45,47,49,56,57 mHealth enables selfmonitoring, self-management, self-medication, overcomes issues of anxiety that can be experienced in crowded environments such as clinics, hospitals or even malls, and it enables patients to live alone and increase their health literacy. Themes of understanding and visibility were mentioned in 8/60 occurrences (13%).…”
Section: Facilitatorsmentioning
confidence: 99%
“…23,30,31,33,35,36,38,41,45,47,[49][50][51][52][53][54][55][56][57][58][59] Table 1 illustrates and rank orders the themes from analysis of the facilitators of adoption based on frequency of their occurrence in the literature.…”
Section: Facilitatorsmentioning
confidence: 99%
“…(1) The conventional wisdom that an attention control group automatically makes a trial more scientifically rigorous is no longer universally accepted (13Y15). First, it may be difficult to achieve an equal amount of attention in both groups, as shown in the trial by Blumenthal et al, where the CST group sessions were on average nearly three times as long as the control group sessions (32.6 versus 10.8 minutes).…”
Section: Editorial Commentmentioning
confidence: 99%
“…In this issue of Psychosomatic Medicine, two trials exemplify different approaches to the emerging paradigm of distance therapy (1,2). These two studies targeted psychological and somatic symptoms as well as quality of life (QoL), which are conditions that especially lend themselves to treatment outside the clinic walls (3Y7).…”
mentioning
confidence: 99%
“…Quite different approach was proposed by Blumenthal et al [8], who compared in a randomized clinical trial coping skills training intervention (by helping them develop skills for coping more effectively with their disease) with COPD education for improving QoL and medical outcomes in COPD patients. The authors concluded, that a telehealth coping skills training intervention produced clinically meaningful improvements in quality of life and functional capacity, but no overall improvement in risk of COPD-related hospitalization and all-cause mortality.…”
mentioning
confidence: 99%